2016
DOI: 10.2147/ott.s112364
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activities of epigallocatechin-3-gallate against cholangiocarcinoma cells

Abstract: PurposeEpigallocatechin-3-gallate (EGCG) is an antioxidant agent derived from green tea. Because it has chemopreventive and anti-invasive effect against various cancer cells, EGCG can be used to inhibit proliferation and invasion of cholangiocarcinoma (CCA) cells.MethodsThe anticancer effects of EGCG were studied using human CCA cells (HuCC-T1). Apoptosis was analyzed by Western blotting. Invasion and migration of cancer cells were assessed with Matrigel® and wound healing assays. An animal tumor xenograft mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…Generally, apoptosis is induced via two pathways, a cell death extrinsic pathway and a mitochondria‐dependent intrinsic pathway. Previous reports have concluded that EGCG induced caspase‐mediated apoptosis in several solid tumour cells, including chondrosarcoma, gastrointestinal stromal tumour, cholangiocarcinoma, esophageal cancer, pancreatic cancer and prostate cancer . EGCG also induced apoptosis in several types of leukaemia.…”
Section: Discussionmentioning
confidence: 95%
“…Generally, apoptosis is induced via two pathways, a cell death extrinsic pathway and a mitochondria‐dependent intrinsic pathway. Previous reports have concluded that EGCG induced caspase‐mediated apoptosis in several solid tumour cells, including chondrosarcoma, gastrointestinal stromal tumour, cholangiocarcinoma, esophageal cancer, pancreatic cancer and prostate cancer . EGCG also induced apoptosis in several types of leukaemia.…”
Section: Discussionmentioning
confidence: 95%
“…19 EGCG also reported to initiate the mitochondrial pathway of apoptosis in different cancer cells [47][48][49] as well as in HeLa cells. 19 EGCG also reported to initiate the mitochondrial pathway of apoptosis in different cancer cells [47][48][49] as well as in HeLa cells.…”
Section: Discussionmentioning
confidence: 96%
“…Tumor growth was significantly reduced in HuCC-T1 tumor-bearing mice subcutaneously injected with EGCG. Notch1 was found to be markedly reduced by EGCG treatment [51].…”
Section: Regulation Of Notch Pathwaymentioning
confidence: 90%